Literatur Review: Prospects of Stem Cell Secretomes for the Treatment of Hair Loss/Alopecia - Nella Novita; Marlina Marlina; Regina Andayani (Poltekkes Kemenkes Riau, 2023)
The goal of this literature review is to find out the role of MSC in stimulating hair growth, particularly in people who suffer from hair loss/alopecia. Literature reviews were conducted using an electronic database such as Researchgate, PubMed, GoogleScholar, and ScienceDirect. MSC secretome for hair growth, secretome for hair growth, ADSC-Exosome for hair growth, ADSC-CM for alopecia, secretome conditioned medium for baldness, and formulation of hair tonic preparations to stimulate hair growth were the keywords used. From these keywords, 13 relevant research articles were found, 11 of which used patients with alopecia as research subjects in randomized clinical trials to examine hair growth. MSC therapy for alopecia has been shown to stimulate hair growth, density, and thickness.